The City Electric : Infrastructure and Ingenuity in Postsocialist Tanzania. - Degani, Michael (Durham : Duke University Press, 2022)
Michael Degani explores how electricity and its piracy in Dar es Salaam, Tanzania, has become a key site for urban Tanzanians to enact, experience, and debate their social contract with the state.
Cover -- Contents -- Acknowledgments -- Introduction. Ethnography of(f) the Grid -- One. Emergency Power: A Brief History of the Tanzanian Energy Sector -- Two. The Flickering Torch: Power and Loss after Socialism -- Three. Of Meters and Modals: Patrolling the Grid -- Four. Becoming Infrastructure: Vishoka and Self-Realization -- Conclusion. The Ingenuity of Infrastructure -- Notes -- Works Cited -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W -- Z.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books